In situ synthesis and characterisation of chitosan/nanohydroxyapatite composite - Ahmad Azraie Mat Zulkipli (N/A, 2015)
In situ synthesis and characterisation of chitosan/nanohydroxyapatite composite by Ahmad Azraie Mat Zulkipli